Molecular phylogeny, diversity, symbiosis and discover of bioactive compounds of endophytic fungi associated with the medicinal Amazonian plant Carapa guianensis Aublet (Meliaceae). (April 2015) - Ferreira, Mariana Costa; Vieira, Mariana de Lourdes Almeida; Zani, Carlos Leomar; Alves, Tânia Maria de Almeida; Junior, Policarpo Ademar Sales; Murta, Silvane M.F.; Romanha, Alvaro Jose; Gil, Laura Helena Vega Gonzales; Carvalho, Amanda Gomes de Oliveira; Zilli, Jerri Edson; Vital, Marcos José Salgado; Rosa, Carlos Augusto; et al.
Abstract: We investigated the endophytic fungal community associated with the Amazonian medicinal plant Carapa guianensis and its potential for providing bioactive compounds. A total of 162 endophytic fungal isolates were obtained and identified by molecular methods. These isolates were classified into 35 different taxa in the genera Aspergilllus, Beltrania, Botryosphaeria, Colletotrichum, Diaporthe, Endomelanconiopsis, Fusarium, Guignardia, Pestalotiopsis, Phomopsis, Pilidiella, Trichoderma, and Xylaria . The most frequent colonisers recovered of C. guianensis were Colletotrichum sp. 1, Diaporthe cf. mayteni, and Pestalotiopsis sp. 1. The fungal community had a moderate richness but high diversity and evenness indices. Colletotrichum sp. and Pilidiella wangiensis displayed selective antibacterial activity; Diaporthe cf. mayteni and Endomelanconiopsis endophytica showed high activity against amastigote forms of Trypanosoma cruzi ; and Colletrotrichum sp. Guignardia mangiferae, Pestalotiopsis sp., and Diaporthe melonis were able to inhibit yellow fever virus proliferation. Our results suggest that the plants living in the tropical forest, such as the Amazonian hotspot region, can live in symbiosis with hidden and underestimated rich communities of endophytic fungi, which deserve protocols and/or specific laws to keep its future conservation. The capability of these endophytic fungi to produce bioactive compounds may be part of their chemical defense and adaptive response to survive and colonizing the plant host in wild environment. Consequently, these fungal communities may provide a source of bioactive molecules, including those able to inhibit or control neglected tropical diseases. Highlights: We examine the endophytic fungi of the medicinal Amazonian plant Carapa guianensis . We discovered bioactive compounds from endophytic fungi. Endophytic fungi may provide a source of bioactive molecules against neglected tropical diseases.